A MULTI-STAGE VALIDATION OF AN INTERIOR DESIGN MODEL FOR PSYCHOLOGICAL WELL-BEING - Dananjaya, Ahmad (Institut Teknologi Nasional Yogyakarta, 2026)
Abstract Traditional interior design often prioritizes aesthetics over users' psychological needs, while existing Human-Centered Design (HCD) approaches remain intuitive. This research proposes and validates a